Protective effect of Myrtle (Myrtus communis) on burn induced skin injury. Issue 8 (December 2019) - Ozcan, Ozan; Ipekci, Hazal; Alev, Burcin; Ustundag, Unsal Veli; Ak, Esin; Sen, Ali; Alturfan, Ebru Emekli; Sener, Goksel; Yarat, Aysen; Cetinel, Sule; Akbay, Tugba Tunali
Highlights: Oxidative system disturbances and skin tissue factor activity are important points in burn injury. Myritus communis (Myrtle) has potential for the treatment of burn induced injury. Antioxidant therapeutic strategies can be considered a promising step in burn management. Abstract: Thermal skin burns cause local injury as well as triggers acute systemic inflammation response where the imbalance between oxidative and antioxidative system occurs. As an alternative treatment, various medicinal herbs are used to treat burn injuries in many countries. In this study, the possible protective role of oral or topical Myrtle ( Myrtus communis L.) treatment against burn-induced damage was investigated. The dorsum of the Wistar Albino rats was shaved and exposed to 90 °C water bath in burn group or 25 °C water bath in control group for 10 s under ether anesthesia. Myrtle extract was applied 100 mg/kg/day for 2 days either orally or topically. In skin samples; malondialdehyde and glutathione levels, catalase, superoxide dismutase, nitric oxide and tissue factor activities were determined. Skin tissues were also examined by light microscopy. Severe thermal skin burn injury caused a significant decrease in glutathione level, superoxide dismutase, catalase and tissue factor activities as well as nitric oxide level, which was accompanied with significant increases in skin malondialdehyde level. Myrtle treatment reversed all these biochemical indices except topical Myrtle treated group's nitric oxide level, as well as histopathological alterations, which were induced by thermal trauma. Both oral and topical Myrtle extract treatment was found to have protective role in the burn induced oxidative injury, which may be attributed to the potential antioxidant effect of Myrtle. As a conclusion, Myrtle significantly diminishes burn-induced damage in skin.